Fundações superficiais: controle de concepção e execução para evitar manifestações patológicas nas edificações - Carvalho, Letícia Moreira de (Universidade Federal Rural do Semi-Árido, 2019)
A well-designed project plays a key role in achieving a satisfactory construction result. Attention in the constructive steps is essential to avoid future problems in the structure that affect its safety and durability, in addition to preventing extra costs. Thus, the objective of this study was to analyze the possible causes of the pathology of foundations in a building, with the purpose of avoiding problems, in the design and execution phases of these elements. The research was done in the literature related to the subject and a case study was done referring to a construction site located in the city of Pau dos ferros, RN. With this, it was observed at the conception stage that the investigation of the soil was insufficient, not being realized the number of holes required according to the norm. In the execution phase, one of the shoes was with the pillar outside the plumb line, which could alter the covering of the reinforcement exposing it and leaving it propitious to oxidation, which could result in the displacement of the concrete. There was also the excessive inclination of the concrete launching ramp as well as non-flat access, which could cause segregation of the concrete. Comparing these and other factors with the literature, it can be concluded that they can cause foundations pathologies such as differential stresses that damage the structure and can generate costs with repairs or even collapse of the structure.
Monografia
Keywords: Patologia das fundações; problemas; concepção; execução; estrutura; Pathology of foundations; conception; execution; structure; ENGENHARIAS::ENGENHARIA CIVIL